Antioxidative Stress and Hepatoprotective Activities of Leaf Extract and Fractions of Setaria megaphylla in Plasmodium berghei Infected Mice - Ndanti Bartholomew William; Augustine Lawrence Bassey; John Akpan Udobang; Jude Efiom Okokon (Biology, Medicine, & Natural Product Chemistry, 2023)
Setaria megaphylla (Steud) Dur & Schinz (Poaceae), a perennial grass used traditionally in the treatment of various diseases such as malaria was, investigated for antioxidative stress activity in Plasmodium berghei-infected mice. The leaf extract (200-600 mg/kg) and fractions (hexane, dichloromethane, ethyl acetate and methanol; 400 mg/kg) of S. megaphylla were investigated for antioxidative stress and hepatoprotective activities in Plasmodium berghei-infected mice using a modified suppressive test model. Antioxidative stress and hepatoprotective potentials were assessed by determining oxidative stress markers levels, liver function indices and histopathology of liver. The extract/fractions progressively reduced parasitaemia induced by chloroquine-sensitive P. berghei infection with the methanol fraction exerting the highest activity. The leaf extract and fractions caused significant (p<0.05 0.001) increases in the levels of oxidative stress markers enzymes and molecules (SOD, CAT, GPx, GSH) and also reduced MDA level significantly (p<0.05) in the livers of the treated-infected mice. The extract/fractions treatment caused reduction in liver enzymes (ALT, AST and ALP), total and conjugated bilirubin. Histology of livers revealed absence or significant reductions in pathological features in the treated infected mice compared to untreated infected mice. The leaf of S. megaphylla may possess antioxidative stress and hepatoprotective effects which may in part be mediated through the chemical constituents of the plant.